QUALITY IMPROVEMENT OF FAST MOVING PARTS PROCUREMENT WITH MULTI ATTRIBUTE FAILURE MODE ANALYSIS (MAFMA) IN A PETRO-CHEMICAL INDUSTRY - Dwi Kurniawan; Ghaista Yumna Margani (President University, 2023)
This paper addressed the problem of high waiting time in a petro-chemical industry in Indonesia. According to Pareto diagram, the procurement process at the industry showed that the number of fast moving item transactions was more than 70% or 19,836 item transactions with 2,524 fast moving material items. The activity of making Purchase Requisition (PR) until the issuance of Purchase Order (PO) for fast moving items required a cycle time of 71.2 days. The highest waste was waiting with a weight of 0.248 and a total of 17 waste items from 27 sub-activities. The average value of sigma for 6 years was 1.79. The application of lean six sigma and MAFMA found that the dominant causes of waste were unfulfilled specified demand and long delivery time. We proposed improvements by enhancing monitoring processes and submitting a contract agreement for the procurement of fast moving spare parts.